Whispers before the flow: a case series on homoeopathic intervention in Pre- Menstrual Syndrome (PMS) - Usha Ghelani Uchat; Ketan Shah; Chintamani Nayak; Mahesh Menon N T; Shunmathy S M (The Bioscan, 2026)
Premenstrual syndrome (PMS) is a common disorder characterized by a combination of emotional, physical, and behavioral symptoms occurring in the luteal phase of the menstrual cycle and significantly affecting quality of life. This case series evaluates the clinical outcomes of individualized homoeopathic treatment using 50-millesimal potencies in three female patients diagnosed with PMS. Each case was assessed using the Shortened Premenstrual Assessment Form (SPAF) to quantify symptom severity at baseline, 3 months, and 6 months. Following detailed case taking, individualized remedies were prescribed in accordance with homoeopathic principles. All three patients showed marked clinical improvement, as evidenced by a consistent reduction in SPAF scores over time. Additionally, the Modified Naranjo Criteria for homoeopathy were applied to assess the causal relationship between the prescribed remedies and therapeutic outcomes, with all cases scoring +9 out of a possible 13. No adverse effects were reported during the treatment course. The results suggest a potential role for individualized homoeopathy in the management of PMS. While promising, these findings are based on a limited number of cases and should be interpreted with caution. Larger controlled studies are warranted to further explore the efficacy and reproducibility of this therapeutic approach.